How To Attain Value for Money Comparing PPP and Traditional Infrastructure Public Procurement - Burger, Philippe (OECD Publishing, 2011)
Governments increasingly use public-private partnerships (PPPs) to pursue value for money. However, value for money is (or at least, should be) the driving force behind traditional infrastructure procurement. Therefore, any project, whether it is a PPP or a traditionally procured project, should be undertaken only if it creates value for money. It seems that the choice between using a PPP or traditional procurement should be simple: governments should prefer the method that creates the most value for money. However, in practice the value-for-money objective is very often blurred, and the choice between using a PPP and traditional infrastructure procurement may be skewed by factors other than value for money. Some factors skew choice towards traditional procurement, while others skew it towards PPPs.